FRAUD DIAMOND FOR DETECTION OF FINANCIAL STATEMENT MISREPRESENTATION IN THE MANUFACTURING INDUSTRY - Rizqi Ayu Mentari; Sopian Sopian (Research In Management and Accounting (RIMA), 2022)
This research was conducted to obtain empirical evidence regarding fraud, primarily due to fraud in financial reports based on the fraud diamond theory. This study tested six independent variables; financial stability, external pressure, financial targets, effective monitoring, rationalization, and capability. P-Score Model is used to detect potential fraudulent financial statements. The objects studied were 103 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019 with 515 annual reports. The results of this study indicate that only two variables have an effect in detecting fraud in financial statements. The variables that have a significant effect are financial stability as proxied by the ratio of changes in assets and financial targets as proxied by the ratio of return on assets (ROA). Other variables represented by external pressure, effective monitoring, rationalization, and capability did not affect the detection of potential fraudulent financial statements. These findings may benefit auditors in predicting fraud in financial statements, considering the fraud diamond environment.